Capitalism Versus Socialism: Can (or Should) Management Scholars Embrace Varieties of Socio‐Economic Systems in a Multipolar World? - Wickert, Christopher (Journal of Management Studies, 2026)
Abstract In an increasingly multipolar world, this Point–Counterpoint debate discusses the imperative for Management and Organization Studies (MOS) to embrace different contexts of socio‐economic systems, specifically varieties of socialism, and in doing so move beyond the predominant capitalist model as a central assumption in the literature. In their Point , Bruton, Li and Gautam argue that MOS has insufficiently embraced socialism as an empirical reality, despite nearly half of the world’s population living in nations reflecting some variety of socialism, in addition to modes of organization following an ethos closer to socialism than capitalism. This view is challenged by the Counterpoint of Foss, Klein, Holmes and Terjesen. While they agree that considering institutional context is vital, they reject the Point’s position, question its imputing of a widespread ‘capitalist bias’, and are concerned that its ethos‐based definitions are imprecise and politically charged. Based on their productive disagreement, collectively this Point–Counterpoint debate underscores the imperative for greater contextualization in MOS more generally, and in entrepreneurship research more specifically, and that organizational goals beyond pure financial profit maximization warrant deeper scholarly attention. This introduction concludes by sketching future research avenues, including configurational institutional analysis, exploring collective motivation in entrepreneurship, and analysing the mechanisms of state control.